Facilitating telemedicine project sustainability in medically underserved areas: a healthcare provider participant perspective - Paul, David L. (BMC Health Serv Res, 2016)
BACKGROUND: Very few telemedicine projects in medically underserved areas have been sustained over time. This research furthers understanding of telemedicine service sustainability by examining teleconsultation projects from the perspective of healthcare providers. Drivers influencing healthcare providers’ continued participation in teleconsultation projects and how projects can be designed to effectively and efficiently address these drivers is examined. METHODS: Case studies of fourteen teleconsultation projects that were part of two health sciences center (HSC) based telemedicine networks was utilized. Semi-structured interviews of 60 key informants (clinicians, administrators, and IT professionals) involved in teleconsultation projects were the primary data collection method. RESULTS: Two key drivers influenced providers’ continued participation. First was severe time constraints. Second was remote site healthcare providers’ (RSHCPs) sense of professional isolation. Two design steps to address these were identified. One involved implementing relatively simple technology and process solutions to make participation convenient. The more critical and difficult design step focused on designing teleconsultation projects for collaborative, active learning. This learning empowered participating RSHCPs by leveraging HSC specialists’ expertise. CONCLUSIONS: In order to increase sustainability the fundamental purpose of teleconsultation projects needs to be re-conceptualized. Doing so requires HSC specialists and RSHCPs to assume new roles and highlights the importance of trust. By implementing these design steps, healthcare delivery in medically underserved areas can be positively impacted.